2023
DOI: 10.1049/gtd2.12879
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced hunter‐prey optimization for optimal power flow with FACTS devices and wind power integration

Abstract: This paper proposes an improved version of the Hunter‐prey optimization (HPO) method to enhance its search capabilities for solving the Optimal Power Flow (OPF) problem, which includes FACTS devices and wind power energy integration. The new algorithm is inspired by the behavior of predator and prey animals, such as lions, wolves, leopards, stags, and gazelles. The primary contribution of this study is to address the tendency of the original HPO approach to get trapped in local optima, by proposing an enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The results demonstrated the strength and efficacy of the ML-TSO approach to solve the OPF problems. An enhanced hunter-prey optimization (EHPO) approach in [7] was suggested to tune the parameters of a FACTS devices and optimize OPF, with wind and solar power. Moreover, it is confirmed that EHPO is robustness to achieve the global search exploration than the conventional hunter-prey optimization (HPO) and the HPO algorithm as well does not success during attaining the optimum solution for the large-scale power systems.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The results demonstrated the strength and efficacy of the ML-TSO approach to solve the OPF problems. An enhanced hunter-prey optimization (EHPO) approach in [7] was suggested to tune the parameters of a FACTS devices and optimize OPF, with wind and solar power. Moreover, it is confirmed that EHPO is robustness to achieve the global search exploration than the conventional hunter-prey optimization (HPO) and the HPO algorithm as well does not success during attaining the optimum solution for the large-scale power systems.…”
Section: B Literature Reviewmentioning
confidence: 99%